Hyper-methylation of Gene Associated with Insensitivity to Arginine Vasopressin in Preeclamptic Placental Vasculature - Gao, Qinqin; Li, Lingjun; Ding, Hongmei; Li, Huan; Tang, Jiaqi; Zhang, Meihua; Li, Ming; Sun, Miao; Xu, Zhice (Medicine and Medical Research: New Perspectives Vol. 1, 2024)
The present study highlights the contractile responses of AVP in normal and pre-eclamptic placental vessels to uncover the distinctive features of placental vascular regulations along with placental pathophysiological changes, as well as the molecular mechanisms of AVP under pre-eclamptic conditions. One of the main causes of maternal morbidity and mortality is pre-eclampsia. Pre-eclampsia is primarily caused by aberrant placental function and circulation, even if the exact mechanisms causing pre-eclampsia are yet unknown. As a potent vasoconstrictor, arginine vasopressin (AVP) has long been associated with regulating placental vascular tone and circulation, and its secretion is significantly elevated in pre-eclamptic circulation. However, little is known about the reactivity of AVP in pre-eclamptic placental vasculature. To uncover the specific characteristics of placental vascular regulations along with placental pathophysiological changes and the corresponding molecular mechanisms under pre-eclamptic conditions, vascular function, and molecular assays were conducted using placental vessel samples from normal and pre-eclamptic pregnancies. The present study found that the vasoconstriction responses of placental vessels to AVP were weakened in pre-eclampsia compared to normal pregnancy. The insensitivity of AVP was correlated with the down-regulated arginine vasopressin receptor 1a (AVPR1A) and protein kinase C isoform \(β\) (PKC\(β\)), especially the hyper-methylation-mediated down-regulation of the AVPR1A and PKC\(β\) genes, respectively. The study findings not only provided new information for comprehending the pathological characteristics of PE but also emphasized the crucial role of epigenetic-mediated gene expression in pre-eclamptic placental vascular dysfunctions. This new and important information may be beneficial for understanding the pathogenesis of PE and for the development of new approaches and treatments for PE.